Ultrasound-Assisted Combined Spinal-Epidural Anesthesia for Cesarean Delivery in a Parturient With Currarino Triad: A Case Report. Issue 11 (3rd June 2019) - Kenevan, Melissa R.; Smith, Hugh M.; Olsen, David A.; Sharpe, Emily E.
Abstract : Currarino triad is a rare hereditary condition characterized by anorectal malformation, sacral dysgenesis, and a presacral mass. Neuraxial anesthetic techniques pose increased risks to patients with spinal malformations. Ultrasound imaging improves accuracy of intervertebral level identification compared to clinical estimation. We present the case of a parturient with Currarino triad and a low conus medullaris undergoing cesarean delivery where preprocedural magnetic resonance imaging and ultrasound imaging allowed for successful combined spinal-epidural anesthesia to be performed. Despite these measures, however, the patient did develop a high spinal and temporary postoperative dizziness.